The relationship between ethical leadership and moral courage : the mediating role of ethical climate and the moderating role of moral disengagement - Şener, Elif Betül (My University, 2025)
Bu çalışmanın amacı ahlaki cesaret, etik liderlik, etik iklim ve ahlaki çözülme arasındaki ilişkiyi incelemektedir. Önemine rağmen, ahlaki cesaret üzerine yapılan ampirik çalışmalar görece sınırlı kalmaktadır. Bu doğrultuda, Türkiye'de özel ve kamu sektörlerinin çeşitli alanlarında çalışan 237 beyaz yakalı katılımcıdan veri toplanmıştır. Katılımcılar demografik bilgi formu, ahlaki cesaret ölçeği, etik liderlik ölçeği, etik iklim ölçeği ve ahlaki çözülme ölçeğinde yer alan sorulara yanıt vermiştir. Elde edilen veriler SPSS 22 programıyla analiz edilmiştir. Analizler sonucunda etik liderliğin hem ahlaki cesarete hem de etik iklimin oluşumuna olumlu katkıda bulunduğu bulunmuştur. Ayrıca etik iklim çalışanların ahlaki cesaret düzeyine katkıda bulunmaktadır. Son olarak etik iklim etik liderlik ve ahlaki cesaret arasındaki ilişkide aracı rolü oynamaktadır. Bu sonuçlar, organizasyonlarda ahlaki cesareti teşvik etmek açısından söz konusu değişkenlerin önemini ortaya koymaktadır.

The purpose of this study is to examine the relationship between moral courage, ethical leadership, ethical climate and moral disengagement. Despite its importance, empirical studies on moral courage remain relatively scarce. In this context, data were collected from 237 white-collar participants working in various fields of the private and public sectors in Türkiye. Participants answered the questions in the demographic information form, moral courage scale, ethical leadership scale, ethical climate scale and moral disengagement scale. The data obtained were analyzed with the SPSS 22 program. As a result of the analysis, it was found that ethical leadership contributes positively to both moral courage and the formation of ethical climate. In addition, ethical climate contributes to the level of moral courage of employees. Finally, ethical climate plays a mediating role in the relationship between ethical leadership and moral courage. These results reveal the importance of those variables for promoting moral courage in organizations.
Keywords: ahlaki cesaret; ahlaki çözülme; Business ethics; ethical climate; ethical leadership; etik iklim; etik liderlik; İş ahlakı; Leadership; Liderlik; moral courage